Aspiration of nasal secretions into the lungs in patients with acute sinonasal infections - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
Objectives: To compare the amounts of nasal secretions aspirated into the lower airway by patients with acute sinonasal infection with that aspirated by healthy adults during sleep. Study Design: Sixteen patients who had received a diagnosis of acute sinonasal infections by accurate history, anterior rhinoscopic examination, and radiological assessment and 13 healthy volunteers, aged 14 to 45 years. Methods: A 10-mCi dose of technetium 99m-labeled macroaggregated albumin (Tc-99m MAA) with a concentration of 1 mCi/mL was prepared at midnight, just before sleep. Each subject was administered two puffs of this spray. At 8 AM the next morning transmission and emission views of the thorax were taken with a gamma camera. Results: No significant difference between the two groups was observed in the amounts of nasal secretions aspirated into the lungs. Conclusions: The amount of nasal secretions aspirated does not increase during acute sinonasal infection. However, by irritating the mucosa of the lower respiratory tracts, bacteria, toxins, and inflammatory products existing in purulent secretions may play a major role in the pathophysiology of asthma and sinusitis.
Keywords: nasal secretions; sinonasal infection; gamma camera; IMMOTILE-CILIA SYNDROME; DISEASE